Production Efficiency Audit on Tea Beverage Agroindustry - Hendra Adiyatna; . Marimin (Jurnal Teknologi dan Industri Pangan, 2001)
The objective of this work was to investigate and to apply economic efficiency performance measurement methods for tea beverage agroindustry. These measurements were based on twelve technique and economic efficiency criteria, which illustrate the condition of the processes. This illustration was able to explain the material and the energy utilization, variance of the processes and product, handling of the waste and acceptance in the market. The methodology was divided into three steps: (1) defining the technique and the economic criteria, appropriate to the circumstance of the processes, (2) state efficiency the level status, (3) evaluation and structure prioritizing of the processes improvement alternatives. The results of this work indicates that there are seven appropriate criteria. The status of the efficiency is in the medium level. The improvement priorities recommended include optimization of material and energy usage and minimization of breaktime of the critical processes.